KEPERCAYAAN TERHADAP PERPINDAHAN MAKAM DI TANJUNG - Sani, Murjani (Jurnal Studia Insania, 2014)
Describing where the moving tomb of Syekh Timur Tengah (hereinafter abbreviated as STT) in Tanjung. The removal of STT was through mediation with the tomb. This tomb is managed to perpetuate the relationship with STTâs spirit and the pilgrims. There is âhaulanâ tradition in every 14 of Shaâban, at that time HA is busy to communicate to the STTâs spirit, showing his encounter with the spirit of the dead in âconsciousâ condition. According to al-Jauzi, the alive people can meet the spirit of the dead through dreams/ conscious based on the al-Zumar verse 42. It said that death is not lost but it is the separation of the body with the spirit. Their meeting is based on Ali âImron verse 169-171 when he gets the blessing from Allah and when his brother who livedin the path of His. This is recognized by the Sufism as Liqa Barzakhi, as experienced by al-Tijani, it is out of ratio range. Meeting of HA and STTâs spirit is assumed as liqa Barzakhi, although it requires further study.